Extraction of Biopolymer and Its Application in Agriculture Wastewater - Lim, Boon Chin (Universiti Teknologi PETRONAS, 2018)
Agriculture sector plays a dominant position in Malaysia as to cater for food demand with increasing population. However, expansion in agricultural anthropogenic processes has resulted in more challenging wastewater treatment due to the increased level of contaminants. This project aims to study the biopolymer extracted from Lepidium Sativum seeds as natural coagulant aid combined with ferric (Fe3+) as a coagulant in coagulation process for turbidity removal to be applied in agriculture wastewater. Characterizations of biopolymer were conducted using Fourier Transform Infrared Spectroscopy (FTIR), zeta potential and Field Emission Scanning Electron Microscopy (FE-SEM). From the FTIR spectra, the biopolymer was assigned by band peaks at 3417.04 cm-1 , 2853.92 cm-1 , 2925.09 cm-1 , 3008.4 cm-1 , 1745.92 cm-1 and 1149.74 cm-1 . The zeta potential of biopolymer was around -16 mV, describing its anionic nature. The morphologies study depicted that the addition of biopolymer produced a more compact and larger structure of the settled sludge.